Una storia, un archivio Idalberto Targioni nell'Italia tra Ottocento e Novecento - Bianchi, Roberto (Biblioteca di storia, 2018)
Idalberto Targioni (1868-1930) was a foundling, peasant, worker, extemporaneous poet, union activist, anti-militarist, socialist and mayor, interventionist and early fascist, man of the regime and lastly a penitent. A controversial figure and protagonist of his time. This volume, through the reorganization of the unpublished papers, the drafting of the archive's consistency list (published here) and the examination of other sources, offers an articulated reconstruction of the life of a significant figure in the Kingdom of Italy. Targioni's story sheds new light on the life of foundlings, peasant culture and socialist municipalism, on the conversions to war and the passages to Mussolinism, on the dynamics within the regime, the contact between public and private dimensions in the biographies of Contemporary Italy.